ANALISIS NILAI PENDIDIKAN KARAKTER MELALUI PROGRAM SHALAT DHUHA DAN LITERASI SEKOLAH DI KELAS II B SD ISLAM TERPADU BUAH HATI SINTANG - Dwi Cahyadi Wibowo; Tedi Suryadi; Felisa Miftahuda (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aims to describe the Value of Character Education Through the Dhuha Prayer Program and School Literacy in Class II B of the Buah Hati Sintang Integrated Islamic Elementary School in the 2022/2023 Academic Year, Sintang District, Sintang District. The method used in this research is descriptive method with a qualitative approach. Data collection tools in the form of field notes, interview sheets, questionnaire sheets, observation sheets and documentation. The results of this study are the implementation of the Dhuha prayer habituation program at the Buah Hati Sintang Integrated Islamic Elementary School which is carried out continuously every day. Duha prayer is carried out in congregation and independently. The implementation of the school literacy movement in shaping student character with class-based activities, school culture-based activities and community-based activities, the value of character education through the Dhuha prayer program and school literacy in class II B of the Buah Hati Sintang Integrated Islamic Elementary School is very good, what do the teachers do? taught is ingrained in the mindset of students. The conclusion is that the cultivation of student character values through the Dhuha prayer program and school literacy in class II B is very good, teachers also apply character values such as being religious, fond of reading, honest, disciplined, tolerant, loving peace and social care. Factors supporting the implementation of Duha prayer and school literacy are facilities and infrastructure, cooperation between teachers and staff. The inhibiting factors are the lack of a place for Duha prayer and a library, and the weather is uncertain. Efforts made by the teacher are habituation, giving examples, role models, awareness, supervision.